Either non-homologous ends joining or homologous recombination is required to repair double-strand breaks in the genome of macrophage-internalized Mycobacterium tuberculosis. - Anna Brzostek (Public Library of Science (PLoS), 2014)
The intracellular pathogen Mycobacterium tuberculosis (Mtb) is constantly exposed to a multitude of hostile conditions and is confronted by a variety of potentially DNA-damaging assaults in vivo, primarily from host-generated antimicrobial toxic radicals. Exposure to reactive nitrogen species and/or reactive oxygen species causes different types of DNA damage, including oxidation, depurination, methylation and deamination, that can result in single- or double-strand breaks (DSBs). These breaks affect the integrity of the whole genome and, when left unrepaired, can lead to cell death. Here, we investigated the role of the DSB repair pathways, homologous recombination (HR) and non-homologous ends joining (NHEJ), in the survival of Mtb inside macrophages. To this end, we constructed Mtb strains defective for HR (ΔrecA), NHEJ [Δ(ku,ligD)], or both DSB repair systems [Δ(ku,ligD,recA)]. Experiments using these strains revealed that either HR or NHEJ is sufficient for the survival and propagation of tubercle bacilli inside macrophages. Inhibition of nitric oxide or superoxide anion production with L-NIL or apocynin, respectively, enabled the Δ(ku,ligD,recA) mutant strain lacking both systems to survive intracellularly. Complementation of the Δ(ku,ligD,recA) mutant with an intact recA or ku-ligD rescued the ability of Mtb to propagate inside macrophages.